The Effect of Antivascular Endothelial Growth Factor Therapy on the Development of Neovascular Glaucoma after Central Retinal Vein Occlusion: A Retrospective Analysis. (1st April 2014) - Ryu, Christina L.; Elfersy, Adrian; Desai, Uday; Hessburg, Thomas; Edwards, Paul; Gao, Hua
Abstract : Purpose . Ischemic central retinal vein occlusion (CRVO) eyes are at high risk of developing neovascular glaucoma (NVG). Our purpose is to investigate the effect of anti-VEGF therapy for macular edema after CRVO on the development of neovascular glaucoma (NVG) in ischemic CRVO eyes. Methods . This is a retrospective case series of 44 eyes from 44 patients with CRVO treated with anti-VEGF therapy for macular edema. The primary outcome was the development of NVG. Results . Of the 44 eyes, 14 eyes had ischemic CRVO, and 30 eyes had nonischemic CRVO. Nonischemic eyes received a mean of 8.4 anti-VEGF doses, over mean follow-up of 24 months. One nonischemic eye (3.3%) developed NVD but not NVG. The 14 ischemic eyes received a mean of 5.6 anti-VEGF doses, with mean follow-up of 23 months. Of these 14 ischemic eyes, two eyes (14%) developed iris neovascularization and 3 eyes (21%) developed posterior neovascularization. Three of these 5 eyes with neovascularization progressed to NVG, at 19.7 months after symptom onset, on average. Conclusion . Anti-VEGF therapy for macular edema may delay, but does not prevent, the development of ocular NV in ischemic CRVO. Significant risk of NVG still exists for ischemic CRVO eyes.